Prediction of Detonation Parameters (95f7a43f-745c-4ae7-ad4e-74c781870372) - P D. Katsabanis (International Society of Explosives Engineers, 1991)
This chapter describes the principles for the derivation of the equations for a detonation wave. The importance of the equation of state for the detonation products is demonstrated and commonly used equations of state are discussed. Furthermore a brief introduction to the TIGER code is presented.